2022
DOI: 10.1002/rmv.2365
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viral co‐infections in patients with COVID‐19 and associated outcomes: A systematic review and meta‐analysis

Abstract: The aim of this systematic review and meta‐analysis was to critically assess the published literature related to community‐acquired viral co‐infections and COVID‐19 and to evaluate the prevalence, most identified co‐pathogens, and relevant risk factors. Furthermore, we aimed to examine the clinical features and outcomes of co‐infected compared to mono‐infected COVID‐19 patients. We systematically searched PubMed, Web of Science, Embase, Scopus, and The Cochrane Library for studies published from 1 November 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 42 publications
(61 reference statements)
6
41
0
Order By: Relevance
“…Likewise, from a public health standpoint, SARS-CoV-2 and influenza virus co-infection combined with variable clinical prognosis poses a greater challenge. A systematic review by Krumbein et al revealed that a higher case-fatality rate was associated with COVID-19 and other viruses' co-infection (13). This is consistent with other studies showing a positive relation between co-infection and increased mortality risk and severity of the disease in these patients (11,14).…”
supporting
confidence: 59%
“…Likewise, from a public health standpoint, SARS-CoV-2 and influenza virus co-infection combined with variable clinical prognosis poses a greater challenge. A systematic review by Krumbein et al revealed that a higher case-fatality rate was associated with COVID-19 and other viruses' co-infection (13). This is consistent with other studies showing a positive relation between co-infection and increased mortality risk and severity of the disease in these patients (11,14).…”
supporting
confidence: 59%
“…Further research will have to show the relevance of our findings in the context of SARS-CoV-2/ influenza virus co-infection. Data on the severity of SARS-CoV-2/ influenza A virus co-infections are inconsistent in cell culture and animal models [Andrés et al, 2022; Kim EH et al, 2022; Kim HK et al, 2022; Oishi et al, 2022] and in humans [Cuadrado-Payán et al, 2020; Yue et al, 2020; Alosaimi et al, 2021; Stowe et al, 2021; Xiang et al, 2021; Krumbein et al, 2022; Swets et al, 2022]. This may not be a surprise, given the differences in interferon signalling between different SARS-CoV-2 variants that we present here and that were described in previous studies [Alfi et al, 2022; Bojkova et al, 2022; Bojkova et al, 2022a; Guo et al, 2022; Thorne et al, 2022].…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of co-infection or superinfection with other viruses, bacteria or fungi is being increasingly reported during the COVID-19 pandemic, though the rate remains relatively low with one study demonstrating 8% rate of bacterial and fungal community-acquired co-infections [ 16 ], and another study citing a rate of 2.1% for bacterial and 0.6% for viral co-infections [ 17 ] during the early stages of the pandemic. A metanalysis demonstrated a pooled prevalence of viral co-infections of 5% with influenza and rhinovirus being the most common, followed by adenovirus and human coronaviruses [ 18 ]. Studies have demonstrated increased severity of COVID-19, more frequent ICU admissions and higher risk of death in co-infected patients [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Case Seriesmentioning
confidence: 99%
“…A metanalysis demonstrated a pooled prevalence of viral co-infections of 5% with influenza and rhinovirus being the most common, followed by adenovirus and human coronaviruses [ 18 ]. Studies have demonstrated increased severity of COVID-19, more frequent ICU admissions and higher risk of death in co-infected patients [ 17 , 18 , 19 , 20 , 21 ]. Incidence of non-SARS-CoV-2 respiratory viruses was significantly impacted by social distancing measures at the start of the pandemic.…”
Section: Case Seriesmentioning
confidence: 99%